Low-lying electronic states of ethanol investigated by theoretical and synchrotron radiation methods. (July 2022) - Barbosa, A. Souza; Mendes, M.; Jones, N.C.; Hoffmann, S.V.; Bettega, M.H.F.; Brunger, M.J.; Limão-Vieira, P.
Highlights: The first complete study to date of ethanol in the 5.64–10.78 eV (220–115 nm) range, together with ab initio theoretical methods in order to provide the most accurate and up-to-date information about the electronic state spectroscopy of ethanol. The most reliable and complete set of absolute photoabsorption cross-sections for this region are given. The observed low energy structure has been assigned to Rydberg and mixed valence/Rydberg transitions. Potential energy curves for the lowest-lying excited electronic states, as a function of the O–H and the C–OH coordinates, are obtained showing rather complex multidimensional character of the potential energy surfaces involved. Abstract: We investigate the ethanol absorption spectrum in the range 5.64–10.78 eV (220–115 nm), by combining ab initio theoretical and experimental methods in order to provide the most accurate and up-to-date information about the electronic state spectroscopy of ethanol. In particular, absolute cross-section values are reported from high-resolution vacuum ultraviolet (VUV) photoabsorption measurements. The present VUV spectrum reveals several new features not previously reported in the literature, with particular reference to the Rydberg ( nd σ, nd σ′ ← (3 a ′′/13 a )), n  ≥ 3 members of the Rydberg ( nd π′( a ′) ← (3 a ′′/13 a )) and n  = 3 members of the Rydberg ( np σ′ ← (10 a ′/12 a )) transitions. The experimental absolute photoabsorption cross sections have subsequently been used to calculate the photolysis lifetime of ethanol in the Earth's atmosphere (0–50 km), showing that solar photolysis is expected to be a weak sink at altitudes lower than 40 km to ● OH radical reactions. Potential energy curves for the lowest-lying excited electronic states, as a function of the O–H and the C–OH coordinates, are also obtained employing the equation of motion coupled cluster single and doubles (EOM-CCSD) and time dependant density functional theory (TD-DFT) methods. These show clear dissociation character at inter-nuclear distances greater than 2.0 Å for the R O–H and 2.2 Å for the R C–OH bond lengths, indicating the rather complex multidimensional character of the potential energy surfaces involved. Graphical abstract: Image, graphical abstract